An Empirical Study on Software Aging of Long-Running Object Detection Algorithms - Pietrantuono, Roberto; Cotroneo, Domenico; Andrade, Ermeson; Machida, Fumio (IEEE International Conference on Software Quality, Reliability and Security (Online), 2022)
Efficient and effective object detection is a key problem in Computer Vision. Numerous object detection algorithms have been developed, whose aim is to achieve two conflicting goals, namely accuracy and efficiency, while being executed in real-time with high robustness. Many of these algorithms must run for an extended period of time, i.e., in video surveillance or in self-driving cars - a working condition that make them subject to the risk of software aging.In this work, we focus on evaluating several object detection algorithms to understand if and to what extent they are affected by software aging. A measurement-based aging approach was adopted, with a series of long-running tests and subsequent data analysis. The results report significant trends of performance degradation, sometimes leading to aging-related failures, as well as memory consumption trends, which turned out to be the main issue across all the experiments.